The consequences of alcoholism caused by socio-economic factors - Porada, Natalia E.; Zhyvitskaya, Elena P. (Journal of the Belarusian State University. Ecology, 2020)
The paper presents an analysis of the dynamics of incidence and mortality of the population of the Republic of Belarus from alcoholism for the period 1995–2016, considers mortality rates from alcohol intoxication as a factor of external influence, describes the relationship between incidence and mortality with the level of alcohol consumption and individual socio-economic parameters. The tendency to decrease of mortality rates of the population from alcoholism and poisoning by alcohol is established. The mortality of the male population from alcohol is 3.6 times higher than the mortality of women, the mortality of the rural population is 2–3 times higher than the urban one. A strong correlation between the incidence of alcoholism and offenses in a state of intoxication, road traffic accidents, mortality from external causes, between alcohol consumption per capita and the number of divorces, the number of employed population was revealed.